Management of temporomandibular joint ankylosis with combination of gap arthroplasty surgery and physiotherapy - Ramadhanty, Nurul; Kasim, Alwin; Tasman, Abel; Adiantoro, Seto; Drajat, Dikki (Padjadjaran Journal of Dentistry, 2016)
Background. Temporomandibular joint (TMJ) ankylosis is a union of the articular surface of the temporal bone to the disc-condyle complex that restricts mandibular movements due to either a fibrous or bony union between the head of the condyle and the glenoid fossa. Common etiological factors are trauma, infection, and pathology in the joint or systemic diseases. The diagnosis of TMJ ankylosis is established through physical and clinical evaluation, and imaging examination. Currently, the surgical techniques used to treat TMJ ankylosis are gap arthroplasty, interpositional arthroplasty, joint reconstruction, and distraction osteogenesis. Purpose. To provide overview about management of temporomandibular joint ankylosis with gap arthroplasty combined with physiotherapy post surgery. Case. A 12-year-old female patient came to Department of Oral and Maxillofacial Surgery with complaint of opening mouth restriction, which occured since one year prior to admission. After complete physical and radiographic examination, patient then was diagnosed with TMJ ankylosis due to neglected odontogenic infection. The treatment was performed with gap arthroplasty under general anesthesia. Patient then underwent physiotherapy after the surgery, including application of heat on the affected region and exercises to open and close mouth. Discussion. Ankylosis of TMJ is an uncommon case that results in chronic and severe limited mouth opening. The critical factor of successful treatment of TMJ ankylosis is early detection, correct surgery approach, implementation of an intensive physiotherapy program, and a good post-operative conduct. Therefore on this patient, gap arthroplasty was the chosen surgery approach followed by intensive physiotherapy. Conclusion.Management goal in TMJ ankylosis isÂ  to increase the patientâs mandibular function, correct associated facial deformity, decrease pain, and prevent reankylosis. Careful surgical technique and subsequent attenÂtion to physiotherapy are both considered essential to achieve a satisfactory result.